2012
DOI: 10.7314/apjcp.2012.13.8.3637
|View full text |Cite
|
Sign up to set email alerts
|

Association Between XRCC5, 6 and 7 Gene Polymorphisms and the Risk of Breast Cancer: A HuGE Review and Meta-analysis

Abstract: Objective: Non-homologous end joining (NHEJ) is a pathway for repairing DNA double-strand breaks. Recent publications indicated that XRCC5, XRCC6 and XRCC7 genes may participate in the pathogenesis of breast cancer. The aim of this Human Genome Epidemiology (HuGE) review and meta-analysis was to investigate associations between XRCC5, XRCC6 and XRCC7 genetic polymorphisms in the NHEJ pathway and breast cancer risk. Methods: Studies focusing on the relationship between genetic polymorphisms in XRCC5, XRCC6 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Our previous studies determined that Ku80 is an important prognostic factor in ESCC . Recent reports suggest that Ku80 is implicated in the development and progression of ESCC, making Ku80 a significant candidate target for ESCC . In this study, we found a positive relationship between the expression of COX2 and Ku80, revealing the diversity and complexity of COX2 in ESCC; thus, our current study added a new mechanism to the function of COX2.…”
Section: Discussionsupporting
confidence: 62%
“…Our previous studies determined that Ku80 is an important prognostic factor in ESCC . Recent reports suggest that Ku80 is implicated in the development and progression of ESCC, making Ku80 a significant candidate target for ESCC . In this study, we found a positive relationship between the expression of COX2 and Ku80, revealing the diversity and complexity of COX2 in ESCC; thus, our current study added a new mechanism to the function of COX2.…”
Section: Discussionsupporting
confidence: 62%
“…It is a DNA repair gene in nonhomologous end joining DNA repair pathway [24]. Genetic polymorphisms of XRCC5 were correlated with multiple cancers, including breast cancer, glioma, and hepatocellular carcinoma [25][26][27]. Up to date, there was no association studies reported between XRCC5 polymorphisms and lung cancer.…”
Section: Discussionmentioning
confidence: 97%
“…Breast cancer may result from multiple environmental, dietary, hereditary, racial, and socioeconomic risk factors [74][75][76][77][78][79][80]. It has been documented that family history, reproductive status, endocrine disorders, and body mass index may play important roles in the development of breast cancer [81,82].…”
Section: Discussionmentioning
confidence: 99%